The Relationship of Knowledge and Attitude of Pregnant Mothers Anemia Trimester III with Compliance with Fe Tablet Consumption in Pasar Kemis Community Health Center, Tangerang Regency - Fatimah Fatimah; Alvina Yasmine Yusuf; Fauza Rizqiya; Revinel Revinel; Tria Astika Endah Permatasari (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
According to 2019 World Health Organization (WHO) data, the Maternal Mortality Rate (MMR) in developing countries associated with anemia in pregnancy due to iron deficiency is 44.3%. One of the most common causes of pregnancy is iron deficiency. This study aims to determine the relationship between compliance to the consumption of Fe tablets in third-trimester pregnant women with knowledge, attitudes, motivation, frequency of ANC, family support, and the role of health workers. This study uses a quantitative method with a cross-sectional approach. Sampling by purposive sampling. The population in this study amounted to 100 respondents. Data collection was collected by distributing printed questionnaires to pregnant women. The research instrument consisted of a questionnaire about the compliance of pregnant women in consuming iron tablets, knowledge, motivation, attitudes, frequency of ANC, family support, and the role of health workers. The results showed that there was a relationship between pregnant women's compliance with knowledge of p-value (0.000), motivation (0.000), attitude (0.000), ANC frequency p-value (0.011), family support (0.002), and the role of health workers (0.000). There is still a lack of compliance among pregnant women in consuming iron tablets at Pasar Kemis Community Health Center, Tangerang Regency as many as 41 people (41.0%).Abstrak: Menurut data World Health Organization (WHO) 2019, Angka Kematian Ibu (AKI) di Negara berkembang yang terkait oleh anemia pada kehamilan dikarenakan difisiensi zat besi sebesar 44,3%. Penyebab paling umum dari kehamilan salah satunya adalah kekurangan zat besi. Penelitian ini bertujuan untuk mengetahui hubungan kepatuhan konsumsi tablet fe pada ibu hamil trimester III dengan pengetahua, sikap, motivasi, frekuensi ANC, dukungan keluarga dan peran tenaga kesehatan. Penelitian ini menggunakan metode kuantiatif dengan pendekatan cross-sectional. Pengambilan sampel dengan purposive sampling. Populasi pada penelitian ini berjumlah 100 responden. Pengumpulan data dikumpulkan dengan menyebarkan kuesioner cetak kepada ibu hamil. Instrumen penelitian terdiri dari kuesioner tentang kepatuhan ibu hamil dalam mengkonsumsi tablet besi, pengetahuan, motivasi, sikap, frekuensi ANC, dukungan keluarga dan peran tenaga kesehatan. Hasil penelitian menunjukkan bahwa terdapat hubungan antara kepatuhan Ibu hamil dengan pengetahuan p-value (0,000), motivasi (0,000), sikap (0,000, frekuensi ANC p-value (0,011), dukungan keluarga (0,002) dan peran tenaga kesehatan (0,000). Masih kurangnya kepatuhan ibu hamil dalam mengkonsumsi tablet besi di Puskesmas Pasar Kemis Kabupaten Tangerang sebanyak 41 orang (41,0%).